MENINGKATKANKEAKTIFANDANHASIL BELAJARPADAKOMPETENSISISTEMSTARTERDANPENGISIAN DENGANMODEL PEMBELAJARANKOOPERATIF TIPE TGT(TEAMSGAMESTOURNAMENT)DI KELAS XI TEKNIK KENDARAAN RINGAN A SMK MA’ARIF 1 KEBUMENTAHUN PELAJARAN 2013/2014 - Lutfil Hakim; Subagyo Subagyo (Universitas Sarjanawiyata Tamansiswa, 2014)
This study aimed to determine : (1) an increase in the activity of student learning through the application of learning models Cooperative Learning Type TGT (Teams Games Tournament) the standard of competence (SK) starter and charging system (2) improving student learning outcomes through the application of learning models Cooperative Learning Type TGT ( Teams Games Tournament ) the standard of competence ( SK ) starting system and charging students of class XIÂ TeknikKendaraanRingan A SMK Maâ€™arif 1 Kebumen Academic Year 2013/2014 .This research was conducted at the research subjects students totaling 36 students . Data collection techniques in this study is the non-test techniques (observations) and test techniques . Non-test techniques ( observation ) is used to determine the activity of students in the study subjects Competency TeknikKendaraanRingan on pre-action , first cycle , second cycle and third cycle.The conclusion of this study : ( 1 ) The application of cooperative learning model TGT ( Teams Games Tournament ) can increase the activity of student learning . This can be seen from the increase in the average activity of students , namely : pre-action at 11 % rising to 32 % in the first cycle , rising to 61 % in the second cycle and increased to 86 % in the third cycle , and ( 2 ) The application of the model learning model cooperative learning TGT ( Teams Games Tournament ) can improve student learning outcomes . This can be seen from the increase in the average value of learning outcomes , namely : pre-action at the average value of only 75.69 rising to 78.47 in the first cycle , rose to 82.04 in the second cycle , and rose to 86.01 in third cycle.